(untitled) (Research, Society and Development, 2020)
The provision of food for schoolchildren is essential for an adequate development of physical and cognitive functions. Therefore, this study aimed to evaluate the adequacy of the menus offered to schoolchildren aged 6 to 15 years enrolled in the public municipal network of Teresina - PI. This is a cross-sectional study carried out in 07 schools, through which energy and macronutrients from menus offered during 01 week were evaluated. The adequacy of nutritional recommendations considered the legislation of the National School Feeding Program, according to the age groups of 6 to 10, and 11 to 15 years. The project received authorization from the Municipal Education Secretariat of Teresina (SEMEC) for execution. It was observed that students from 6 to 10 years old and 11 to 15 years old, presented energy adequacy of 100.96% and 114.94%, in that order. In the range of 6 to 10 years, the adequacy of carbohydrates was slightly higher than that recommended by the PNAE, differing from lipids, which showed deficient values. The percentage of proteins assumed significantly high values, being 135.53% and 182.35% for students aged 6 to 10 and 11 to 15 years, respectively. Therefore, the need for continuous monitoring is evident, as well as for the planning and distribution of school meals with efforts to reach the minimum daily recommendation.